PELATIHAN MODERASI BERAGAMA PADA LEMBAGA PAUD SE-KECAMATAN BAE KABUPATEN KUDUS - Yuliantia, Enny; Hasanah, Nur (Kreasi: Jurnal Pengabdian Masyarakat, 2023)
This Community Service activity aims to provide religious moderation training for early childhood education (PAUD) teachers in Bae District, Kudus, with the training location at RA Sholahiyah. The target audience includes all teachers and school principals in the district, guided by experts and accompanied by experienced students from IAIN Kudus. The methods used include socialization, demonstration, implementation, and monitoring. Socialization and demonstration were conducted by the facilitator through training and simulation of singing methods as a means of instilling religious moderation values. The results of the training showed high enthusiasm and motivation among the teachers to implement religious moderation in their respective schools, which is expected to enhance their creativity and innovation in developing learning activities in PAUD